Peran Kepemimpinan Pendidikan Dalam Membangun Ideologi Di Pondok Pesantren Darul Falah Ponorogo - Iqbal Fitriansyah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Abstract : The purpose of this study is to describe the role of educational leadership in building the ideology of education and the ideology of education built at the Darul Falah Islamic boarding school in Ponorogo. The results of this study found several findings about the ideology of education that was built. 1. The ideology built at the Darul Falah Islamic boarding school is the ideology of moderate education by adhering to the rules of education that have been outlined by the founder since the founding of the pesantren. The rule is "Al-muhafadhotu ala qodimis sholih wal akhdu bi Jadidil Aslah" which means (maintaining good classical cultures and taking constructive new cultures), so Darul Falah develops according to the times, the curriculum used combines Salafiyah and modern. The educational values ​​that are instilled are Panca Jiwa Pondok, including: Sincerity, simplicity, independence, ukhuwah Islamiyah, freedom. 2. The highest educational leadership role in Darul Falah Islamic boarding school is Kyai who is the Chair of the Foundation and oversees the Director of KMI. There are 4 dimensions of Kyai leadership, including: community leaders, scientific leaders, spiritual leaders, and administrative leaders. Structurally, educational leaders cooperate with each other in building the ideology of pesantren education. There are several processes of educational leadership in carrying out the mandate in building the ideology of pesantren education, including: instruction, consultation, participation, and control.   Keywords: Educational Leadership, Islamic Boarding School Educational Ideology